An ontology-based system for intelligent matching of travellers' needs for Group Package Tours. (2nd September 2008) - Kanellopoulos, Dimitris N.
In recent years, the package tour industry has fostered a dependency on technology for its operational and strategic management. However, the existing tools for facilitating searches of availability of package tours do not provide intelligent matching between offered package tours and the personal requirements of the travellers. The objective of this research work was to design an intelligent web portal to serve as service provider in tasks related with package tours. This portal aims at helping people living in Europe to find package tours that match their personal travel preferences. For this purpose, the knowledge of the package tour domain has been represented by means of ontology. Additionally, the ontological component allows for defining an ontology-guided search engine, which provides more intelligent matches between package tours offers and travelling preferences.